DYNAMICS OF THE HALAL TOURISM INDUSTRY IN INDONESIA - Riyani Fitri Lubis; Robi Rendra Tribuana (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
The halal tourism industry in Indonesia has experienced significant growth and holds great potential to become one of the main pillars of the national tourism sector. As the country with the largest Muslim population in the world, Indonesia offers various tourist destinations that can be integrated with the halal tourism concept, including Lombok, Aceh, and West Sumatra. This article explores the dynamics of the halal tourism industry in Indonesia, including its developments, potential, challenges, and opportunities. Through a qualitative approach, this article examines how various aspects such as the provision of halal food, prayer facilities, sharia-compliant accommodations, and Islamic environments are implemented in various tourist destinations. Additionally, the article reviews the support from the government and the role of industry players in promoting and developing halal tourism. The analysis shows that despite challenges such as halal certification standardization and industry awareness, Indonesia has received international recognition as a leading halal tourism destination. Continuous support from the government and innovations from industry players are required to overcome these challenges and capitalize on existing opportunities. With the existing potential and support, Indonesia can strengthen its position as a leading global halal tourism destination, which not only positively impacts the national economy but also enhances the country's image as a destination that is welcoming and respectful of cultural and religious diversity.